Factors that affect learning outcomes in online learning - Aviory, Koryna; Wahyumiani, Nur; Suharni, Suharni (Graduate School of Universitas Negeri Yogyakarta & Himpunan Evaluasi Pendidikan Indonesia (HEPI), 2022)
Online learning is an alternative to learning during a pandemic. This learning is done by utilizing technology and information. Constraints in online learning are taken into consideration so that the expected competencies are achieved. These constraints are also referred to as factors. This study aims to determine the factors contributing to learning achievement during online learning during the pandemic. This research was conducted at SMAN 1 Kalibawang and SMA N 2 Ngaglik, with 90 respondents as the subject of the research trial taken randomly. The instrument used is a questionnaire and the results of math test scores. This research uses the Partial Least Squares-Structural Equation Model (PLS-SEM). The purpose of PLS-SEM is to confirm how well the variables that have been measured can represent the formed factors. The steps taken in conducting analysis using PLS-SEM include: (1) designing an analytical model by making path diagrams; (2) identifying the model; (3) estimating parameters; (4) drawing conclusions. Parameter estimation is divided into two parts: the outer model (measurement model) and the inner model (structural model). The results showed that learning media when online learning had a significant effect on learning achievement. The effect given is 83.3% which has a high effect.